2010
DOI: 10.1016/j.jssc.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and structural transitions of orthorhombic fluorite-related compounds Ln3MO7 (Ln=rare earths, M=transition metals)

Abstract: Magnetic properties and structural transitions of ternary rare-earth transition-metal oxides Ln 3 MO 7 (Ln = rare earths, M = transition metals) were investigated. In this study, we prepared a series of molybdates Ln 3 MoO 7 (Ln = La ~ Gd). They crystallize in an orthorhombic superstructure of cubic fluorite with space group P2 1 2 1 2 1 , in which Ln 3+ ions occupy two different crystallographic sites (the 8-coordinated and 7-coordinated sites). All of these compounds show a phase transition from the space gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 39 publications
0
39
0
7
Order By: Relevance
“…This type of structure allows a wide variety of chemical substitutions at the R and M sites (3+ and 4+ or 2+ and 5+ combinations of valence, as well as oxygen vacancies). The R sites can accommodate all the rare earth ions together with yttrium and have an ordered, defect‐fluorite superstructure . For antimonate compounds, Hinatsu et al reported the detailed crystal structure and magnetic properties of ternary Ln 3 SbO 7 (Ln = rare earths).…”
Section: Introductionmentioning
confidence: 99%
“…This type of structure allows a wide variety of chemical substitutions at the R and M sites (3+ and 4+ or 2+ and 5+ combinations of valence, as well as oxygen vacancies). The R sites can accommodate all the rare earth ions together with yttrium and have an ordered, defect‐fluorite superstructure . For antimonate compounds, Hinatsu et al reported the detailed crystal structure and magnetic properties of ternary Ln 3 SbO 7 (Ln = rare earths).…”
Section: Introductionmentioning
confidence: 99%
“…7),12) On the other hand, Ln 3 MoO 7 compounds which crystallize in the orthorhombic structure with space group P2 1 2 1 2 1 at room temperature transform to the space group Pnma when they are heated above the transition temperature. 43) For any Ln 3 MO 7 compounds, their phase transition temperatures increase with decreasing Ln ionic radius. 9),12),13),31), 43) As for M = Ta compounds, crystal structures and magnetic properties for Ln 3 TaO 7 (Ln = La, Pr, Nd, SmLu) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it creates one oxygen vacancy per fluorite cell. Here cation ordering occurs at the metal site and the oxide‐vacancy occurs at anion site, because of the significant difference in ionic radii of Ln 3+ and M 5+ cation . Photoluminescence properties of Eu 3+ doped R 3 SbO 7 (R=La, Gd, Y) and Sm 3+ doped La 3 SbO 7 were studied by Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Here cation ordering occurs at the metal site and the oxide-vacancy occurs at anion site, because of the significant difference in ionic radii of Ln 3 + and M 5 + cation. [10] Photoluminescence properties of Eu 3 + doped R 3 SbO 7 (R = La, Gd, Y) and Sm 3 + doped La 3 SbO 7 were studied by Wang et al [11] and Li et al [12] respectively. It is reported that this compound has high chemical and thermal stability as well as lattice stiffness.…”
Section: Introductionmentioning
confidence: 99%